Mechanisms of Kaposi's Sarcoma-Associated Herpesvirus Latency and Reactivation - Ye, Fengchun (Hindawi Publishing Corporation, 2011)
The life cycle of Kaposi's sarcoma-associated herpesvirus (KSHV) consists of latent and lytic replication phases. During latent infection, only a limited number of KSHV genes are expressed. However, this phase of replication is essential for persistent infection, evasion of host immune response, and induction of KSHV-related malignancies. KSHV reactivation from latency produces a wide range of viral products and infectious virions. The resulting de novo infection and viral lytic products modulate diverse cellular pathways and stromal microenvironment, which promote the development of Kaposi's sarcoma (KS). The mechanisms controlling KSHV latency and reactivation are complex, involving both viral and host factors, and are modulated by diverse environmental factors. Here, we review the cellular and molecular basis of KSHV latency and reactivation with a focus on the most recent advancements in the field.